Factors affecting face mask-wearing behaviors to prevent COVID-19 among Thai people: A binary logistic regression model - Kaewpan, Wonpen; Rojpaisarnkit, Kunwadee; Pengpid, Supa; Peltzer, Karl (Frontiers in Psychology, 2022)
Objectives: Face mask-wearing is a standard preventive measure, in addition to hand washing and physical distancing. Individuals may find that wearing a face mask protects their physical health and prevents viral transmission (Rojpaisarnkit, Kaewpan, Pengpid & Peltzer, 2022; Fakhira et al., 2021; Doung-Ngern et al., 2020). However, none of the studies in Thailand identified factors associated with face mask-wearing behaviors among Thai people. Therefore, this study aims to determine factors affecting face mask-wearing behaviors to prevent COVID-19. Methods: This research is analytical survey research. The data used in this study was under the project title "The assessment of psychosocial and behavioral response and compliance to restriction measures to prevent and control COVID-19: A series of the rapid survey.” 6,521 people participated in an online survey by multi-stage sampling. Bivariate logistic regression analysis was used to examine the factors associated with face mask-wearing behaviors. Results: After adjusting for independent variables (i.e., gender, age, education, career, smoking, and comorbidity disease), the bivariate logistic regression analysis revealed that gender, age, and career were statistically significant to the face mask-wearing behaviors (p< 0.05). Level of education, smoking, and comorbidity disease was not statistically significant with face mask-wearing behaviors among Thai people. Conclusions: Further study should explore broader on individual face mask perceptions and wearing in the continuing of COVID-19 across gender, age, and careers to better understand their health behaviors and to inform further policy. In addition, the development of an intervention to promote face mask-wearing should target males who age below 30 yrs. and did not work in government services careers as this group of the population was likely not to wear a face mask outside the home.